Pengaruh Ukuran Perusahaan, Profitabilitas, Likuiditas, dan Umur Perusahaan Terhadap Islamic Social Reporting - Musthofa Hadi; Prihatni, Rida; Susanti, Santi (Jurnal Akuntansi, Perpajakan dan Auditing, 2025)
This study aims to determine the effect of company size, profitability, liquidity, and company age on Islamic Social Reporting (ISR). The study utilizes quantitative methods and employs regression analysis to analyze data collected from purposive sampling and use non participant observation. The results of the study indicate that the company size has impact ISR practices, profitability has impact ISR practices, liquidity has not impact ISR practices, company age has impact ISR practices.